Aniline-based hole transporting materials for high-performance organic solar cells with enhanced ambient stability. Issue 28 (7th July 2021) - Phan, Tan Ngoc-Lan; Kim, Jinseck; Kim, Geon-U; Lee, Seungjin; Kim, Bumjoon J.
Abstract : Our work suggests the design of new hole transport material, a protonic acid-doped oligo(aniline), for achieving both high device efficiency and improved operational stability of organic solar cells. Abstract : The selection of interfacial layers in organic solar cells (OSCs) is crucial for enhancing their power conversion efficiency (PCE) and operational stability. PEDOT:PSS is the most widely used hole transport layer (HTL) for high-performance OSCs; however, device stability is often severely degraded, owing to the strong acidity and hygroscopicity of PEDOT:PSS. Herein, we report a new efficient HTL system comprising an oligo(aniline) host (PBD) and an aryl sulfonic acid dopant (PFBSA), and demonstrate its use in high-performance OSC devices. Desirable properties like solvent orthogonality, high transmittance, excellent conductivity, and appropriate work function establish the suitability of the PBD:PFBSA film as an HTL. Thus, a PBD:PFBSA HTL is employed in the PM6:Y6-based OSC system to achieve a PCE of 15.24%, which is comparable to that of the PEDOT:PSS HTL-based OSC. Importantly, the PBD:PFBSA HTL-based OSC exhibits significantly higher device stability than the PEDOT:PSS HTL. We investigate the film properties of the PBD:PFBSA HTL to elucidate the origin of the superior device stability. Our results highlight the successful design of a protonic acid-doped oligo(aniline)-based material and its practical application as an effective HTL for OSCs.